The Effectiveness of Connectivism Theory-Based Learning Media in Improving Digital Islamic Literacy - Abdul Rahim; Rusli; Linda Lestari; Ani Pratiwi; Juharmin Suruambo (AIQU: Journal Multidiscipliner of Science, 2025)
The digital transformation in education necessitates innovative approaches in the development of learning media, including in Islamic Religious Education (IRE). One of the most relevant approaches to the information era is connectivism theory, which emphasizes the importance of knowledge networks in the learning process. This study aims to analyze the effectiveness of connectivism-based learning media in enhancing students’ digital Islamic literacy, defined as the ability to access, evaluate, and utilize Islamic information critically, ethically, and contextually through digital media. This research employed a qualitative approach using library research methods, analyzing primary and secondary sources related to connectivism, instructional media, and digital Islamic literacy. Data were thematically analyzed through interpretive and critical methods based on relevant scholarly literature. The findings indicate that implementing connectivism-based learning media is effective in promoting students’ active participation in Islamic digital knowledge networks, improving critical thinking skills toward online religious content, and fostering moderate religious attitudes. However, challenges such as limited technological access and teacher readiness remain significant barriers to implementation in certain educational settings. The study concludes that connectivism offers a strong theoretical foundation for designing IRE learning media that are contextual, interactive, and aligned with 21st-century educational characteristics. The research recommends the development of a connectivism-oriented digital IRE curriculum and intensive training programs for educators to support effective implementation.